스마트홈 서비스 유형 재분류에 관한 연구: 행동인터넷(IoB)과 개인정보 활용을 중심으로 - 유승현(Seung-Hyun Yu); 곽은아(Eun-A Kwak); 박만수(Man Su Park) (디지털콘텐츠학회논문지, 2022)
본 연구는 스마트홈이 빠르게 진화하고 새로운 영역으로 확장되고 있는 상황에서 스마트홈 서비스 유형을 재분류하고 이를 논의하는데 초점을 두었다. 스마트홈 서비스를 IoB 관점으로 새롭게 조망하고, 스마트홈 서비스에서 활용되는 개인정보의 문제를 논의하였다. 그리고 이를 바탕으로 스마트홈 서비스 유형을 재분류하였다. 무엇보다 기존 연구와 달리 스마트홈 서비스를 이용자 관점(인간 행동, 개인정보 활용 정도)에서 개념화화고 유형화하여 재분류하였다. 결과적으로 스마트홈 서비스 유형을 크게 생활, 건강, 안전, 문화, 교육 등으로 분류하고, 세부적인 서비스 분야를 제시하였다. 새로운 유형 분류기준에서 주목할 부분은 개인정보 활용 정도이다. 스마트홈 서비스가 소비자 친화적인 서비스이자 이용자 관점의 서비스가 중심이 될 수 있기 때문에 개인정보 활용의 문제는 선행되어야 할 과제이다. 향후에는 개인정보 보호를 위한 모델 및 기술 개발 그리고 이를 기반으로 하는 서비스 확장이 필요할 것이다. This study focused on reclassifying smart home service types and discussing them in a situation where smart home is rapidly evolving and expanding into new areas. The smart home service is newly viewed from the point of view of IoB, and the problem of personal information used in the smart home service is discussed. And based on this, smart home service types were reclassified. This study focused on reclassifying smart home services by conceptualizing and categorizing them from the user's point of view(human behavior, degree of personal information use). As a result, smart home service types are broadly classified into living, health, safety, culture, and education, and detailed service fields are presented. What is noteworthy in the new classification criteria is the degree of personal information use. Since the smart home service is a consumer-friendly service and a service from the user's point of view can be central, the issue of personal information utilization is a task that must be preceded. In the future, it will be necessary to develop a model and technology for personal information protection and to expand services based on it. KCI Citation Count: 0